Development of a CFD simulation for the analysis of CO2 separation percentage using novel [emim][C2N3] ionic liquid solution inside the gas–liquid contactor - Adel Alhowyan; Wael A. Mahdi; Ahmad J. Obaidullah (Scientific Reports)
Abstract Growing emission of environmentally-hazardous greenhouse pollutants (especially CO2) has motivated the researchers to apply gas–liquid membrane contactors as an easy-to-operate and cost-effective technique for increasing their separation efficiency from different sources. In the current decades, ionic liquids (ILs) have shown their potential in the gas separation industry owing to their noteworthy advantages such as great capacity, excellent adjustability and suitable thermal/chemical stability compared to commonly-employed amine absorbents. This investigation aims to analytically/numerically determine the separation yield of CO2 from CO₂/N2 gaseous flow using novel -Ethyl-3-methylimidazolium dicyanamide ([emim][C2N3]) IL inside the gas–liquid contactor. To fulfill the ultimate purpose, a CFD simulation has been proposed using COMSOL Multiphysics software to predict the results. Comparison of model outcome with experimental data has shown brilliant concurrence with the average relative deviation of almost 5%. Evaluation of the results has shown the excellent performance of [emim][C2N3] IL for the removal of CO2 (Separation efficiency of around 100%). Finally, the effects of some module/membrane parameters on increasing or decreasing the separation efficiency has been studies in detail.